Impact of liquidity risks on financial performance: Evidence from Sri Lanka's Licensed Commercial bank after the Basel III regulatory requirements - Yogendrarajah, R.; Mithila, G. (University of Jaffna, 2023)
Commercial banks play an important role in the financial system stability of the country (Drig:i and Dura, 2014) which draw treat research attention on risks taken by banks specially on liquidity risk. According to Drehmann and Nikolaou (2013), liquidity risk is when banks are unable to settle its short term obligation on time. Liquidity assets mismatch, economic crisis, management's inability to measure the liquidity requirements are some of the reasons which lead depositors to withdraw deposits and cause the particular bank to fail or entire banking system to collapse through contagion impact (Madhuwanthi & Morawakage, 2019). Many researchers (Driga and Dura, 2014; Drehmann and Nikolaou, 2013; Madhuwanthi & Morawakage, 2019) found contrary relationships between the liquidity risks of the banks and performance level. Therefore, the objective of the study is to examine the impact of liquidity risks on financial performance of licensed commercial banks in Sri Lanka after BASEL Ill implementation.
Keywords: Liquidity Risk management; Net Stable Funding ratio; Liquidity Coverage Ratio; Financial Performance; Commercial Banks